Energy Transformation – The Polish case - Dorota NIEDZIOLKA; Bartosz SOBIK (Communications of International Proceedings, 2021)
This article focuses on vital issue of energy transformation in Poland in the context of situation on energy markets and energy policy in European Union (EU). The main purpose of this publication is to indicate the challenges and conditions for energy transition, particularly in terms of energy security. Authors proved that energy transformation is an important prerequisite for changing the structure of the energy market and is a reflection of the structural changes taking place in the economy. Energy market in Poland has been experiencing intensive changes for almost three decades. Currently, in compare to energy systems across West Europe, Polish energy system is still based on coal technologies. Despite the rapid growth of renewable energy sources, there is a significant investment gap, which could occur a threat for security of supply electric energy. Implementation of investments in the power sector is a key element of the energy transition aimed at decarbonisation of the electricity generation sector in Poland. The energy transition currently taking place in Poland is forcing a change in the energy mix - from coal-based to a diversified energy mix using renewable and gas-based power plants. Rapidly rising CO2 emission allowance prices will increase the pace of decarbonisation due to deepening unprofitability of coal-based power generation. The energy sector in Poland differs from those in Western or Southern Europe and will face a number of significant challenges in the coming years to achieve the goal of sustainable energy transition.
Keywords: Energy Transition; Energy Market; Climate; Decarbonization.